2016
DOI: 10.4103/0019-5413.189602
|View full text |Cite
|
Sign up to set email alerts
|

Human autologous mesenchymal stem cells with extracorporeal shock wave therapy for nonunion of long bones

Abstract: Background:Currently, the available treatments for long bone nonunion (LBN) are removing of focus of infection, bone marrow transplantation as well as Ilizarov methods etc. Due to a high percentage of failures, the treatments are complex and debated. To develop an effective method for the treatment of LBN, we explored the use of human autologous bone mesenchymal stems cells (hBMSCs) along with extracorporeal shock wave therapy (ESWT).Materials and Methods:Sixty three patients of LBN were subjected to ESWT trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In 22 of the cases, pulsed electromagmetic field (PMEF) therapy was also applied without achieving significantly increased healing rates [38]. Zhai et al reported that significantly higher union rates of long-bone non-unions were obtained when applying autologous mesenchymal stem cells additionally to fESWT [39]. To the best knowledge of the authors, the present study describes the combination of fESWT, a biophysical procedure, with nail dynamization for the first time.…”
Section: Discussionmentioning
confidence: 91%
“…In 22 of the cases, pulsed electromagmetic field (PMEF) therapy was also applied without achieving significantly increased healing rates [38]. Zhai et al reported that significantly higher union rates of long-bone non-unions were obtained when applying autologous mesenchymal stem cells additionally to fESWT [39]. To the best knowledge of the authors, the present study describes the combination of fESWT, a biophysical procedure, with nail dynamization for the first time.…”
Section: Discussionmentioning
confidence: 91%
“…Our review included two randomized controlled trials (RCTs) [ 28 , 34 ], one non-randomized controlled trial [ 35 ], and 20 observational studies (14 retrospective [ 5 , 9 , 25 , 26 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and six prospective [ 11 , 46 , 47 , 48 , 49 , 50 ]). Together, the included papers reported a total of 1838 cases of delayed union or nonunion ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The average Downs and Black score for the 23 included studies was 15.2 (range 8–26), which is at the low end of the fair range. Only one study scored within the excellent range [ 28 ], and only two scored within the good range [ 33 , 34 ]. Ten papers had fair scores [ 5 , 26 , 36 , 37 , 38 , 39 , 43 , 46 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…In clinical work, a fracture with no signs of healing over 6 months is usually defined as fracture nonunion [ 20 ], and there have been a large number of studies and articles on healing fracture nonunion. Studies have shown that ESW can promote bone formation, induce angiogenesis, ease pain, and stimulate callus growth, as well as a variety of biological effects [ 21 23 ].…”
Section: Discussionmentioning
confidence: 99%